Effect of planting methods, Mycorrhiza and zinc fertilization on growth and grain yield of pearl millet (Pennisetum glaucum) - RAMNIWAS,; KUMAWAT, S M; OLA, GOGRAJ; GAUTAM, PRIYANKA; BHUNIA, S R; JAKHAR, R K; NITHARWAL, PRAVEEN KUMAR; CHOUDHARY, LAKSHAY; GORA, M K; JAT, S L; KAKRALIYA, MANISH (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) seasons of 2020 and 2021 at research farm of Swami Keshwanand Rajasthan Agriculture University, Bikaner, Rajasthan to study the effect of planting methods, Mycorrhiza and zinc fertilization on growth and productivity of pearl millet [Pennisetum glaucum (L) R.Br.] in hot arid region. The experiment comprised 24 treatments combination having 3 planting methods (S1, flat bed; S2, ridge and furrow; S3, pit technique) and two Mycorrhiza level (M0, control; M1, 8 kg/ha Mycorrhiza basal) in main plot and 4 zinc fertilization practices (Z0, control; Z1, 0.5% ZnSO4 two foliar spray; Z2, zinc sulphate @10 kg/ha basal + 0.5% foliar spray and Z3, zinc sulphate @20 kg/ha basal) in sub plots were laid out in split-plot design and replicated thrice. It may be inferred that in pearl millet pit planting technique (S3), Mycorrhiza (M1) + fertilized with zinc sulphate (Z2) practice gave significantly higher growth parameters, viz. plant stand (141.20 thousand/ha), plant height (171.1 cm), dry matter accumulation, crop growth rate, relative growth rate, chlorophyll content (4.3 mg/g), root dry weight (9.8 g/plant) and number of green leaves/plant (13.9 no./plant), quality parameters, viz. protein content (12.5%) and protein yield (384 kg/ha) in grain, ash (12.1%) and fibre content (44.3%) in stover and grain yield (3.1 t/ha) as compared to all other treatment combinations on pooled basis. The findings emphasize the potential of this technique for enhancing pearl millet productivity and quality in hot arid regions.